US patent no. 7,726,203: Multiphase coriolis flowmeter - Mattar, WM; Henry, M; Duta, MD; Tombs, M (United States Patent and Trademark Office, 2010)
A flowmeter is disclosed. The flowmeter includes a vibratable flowtube, and a driver connected to the flowtube that is operable to impart motion to the flowtube. A sensor is connected to the flowtube and is operable to sense the motion of the flowtube and generate a sensor signal. A controller is connected to receive the sensor signal. The controller is operable to determine a first flow rate of a first phase within a two-phase flow through the flowtube and determine a second flow rate of a second phase within the two-phase flow.